2004
DOI: 10.1021/ic035289a
|View full text |Cite
|
Sign up to set email alerts
|

Selective Dehydrogenation of Amines with Respect to Coordination Geometry:  Different Oxidation Products of Tricyano[bis(2-pyridylmethyl)amine]ferrate(II) between mer- and fac-Isomers

Abstract: Both the fac- and mer-isomers of tricyano[bis(2-pyridylmethyl)amine = 2-DPA]ferrate(II) were isolated and their spectroscopic properties compared. The fac-isomer was converted to the corresponding iron(III) complex under acidic conditions. Oxidation of the ferrate(II) complexes with ammonium peroxodisulfate yielded the mer-isomer of the dehydrogenated ferrate(II) compound, but only the metal-oxidized iron(III) complex for the fac-isomer was produced under neutral or basic conditions. Electrochemical measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 32 publications
0
35
0
Order By: Relevance
“…In 1983, Keene et al reported that Δ-[Ru­(bpy) 2 ( R -Meampy)] 2+ and Λ-[Ru­(bpy) 2 ( S -Meampy)] 2+ [Meampy is 2-(1-aminoethy1)­pyridine] diastereomers have different oxidation rates under chemo- and electro-oxidation conditions . Twenty years later, Kurosaki et al found that only the mer -[Fe­(2-DPA)­(CN) 3 ] − [2-DPA is bis­(2-pyridylmethyl)­amine] isomer was oxidized into the imine complex in the presence of ammonium peroxodisulflate as an oxidant . Inspired by these findings, we have observed the photoreaction of Δ-[Ir­(pq) 2 ( d -pro)] and Δ-[Ir­(pq) 2 ( l -pro)] diastereomers and found the oxidation dehydrogenation rate of Δ-[Ir­(pq) 2 ( l -pro)] is ∼60 times faster than that of Δ-[Ir­(pq) 2 ( d -pro)] .…”
Section: Results and Discussionmentioning
confidence: 66%
“…In 1983, Keene et al reported that Δ-[Ru­(bpy) 2 ( R -Meampy)] 2+ and Λ-[Ru­(bpy) 2 ( S -Meampy)] 2+ [Meampy is 2-(1-aminoethy1)­pyridine] diastereomers have different oxidation rates under chemo- and electro-oxidation conditions . Twenty years later, Kurosaki et al found that only the mer -[Fe­(2-DPA)­(CN) 3 ] − [2-DPA is bis­(2-pyridylmethyl)­amine] isomer was oxidized into the imine complex in the presence of ammonium peroxodisulflate as an oxidant . Inspired by these findings, we have observed the photoreaction of Δ-[Ir­(pq) 2 ( d -pro)] and Δ-[Ir­(pq) 2 ( l -pro)] diastereomers and found the oxidation dehydrogenation rate of Δ-[Ir­(pq) 2 ( l -pro)] is ∼60 times faster than that of Δ-[Ir­(pq) 2 ( d -pro)] .…”
Section: Results and Discussionmentioning
confidence: 66%
“…On the basis of the previous findings that the photoreactions of AA complexes are diastereoselective at room temperature, ,, the diastereomeric complexes of hpro were prepared by the reaction of enantiopure Δ-[Ir­(pq) 2 (MeCN) 2 ]­(PF 6 ) with d -hpro or l -hpro. The photoreactivity of Δ-[Ir­(pq) 2 ( l -hpro)] was indeed observed using EtOH as the solvent in the presence of an O 2 atmosphere at 30 °C, as shown in Scheme .…”
Section: Resultsmentioning
confidence: 99%
“…also found only the mer ‐[Fe II (2‐ DPA)(CN) 3 ] – (2‐DPA is bis(2‐pyridylmethyl)amine) isomer was oxidized into imine complex in the presence of (NH 4 ) 2 S 2 O 8 as an oxidant, while the fac ‐[Fe II (2‐DPA)(CN) 3 ] – was converted into fac ‐[Fe III (2‐DPA)(CN) 3 ] under the identical conditions, indicating the geometrical isomerism also significantly influences the oxidative reaction. [ 13 ] Inspired by these findings, we have turned our attention to Ir(III) amino acid (AA) complexes and found that the diastereomers have distinguishable photophysical properties and photoreactivity. [ 14 ] The oxidative dehydrogenation rate of Δ‐[Ir(pq) 2 ( L ‐pro)] ( Δ‐ L , where pq is 2‐phenylquinoline and pro is proline) diastereomer is significantly faster than that of Δ‐[Ir(pq) 2 ( D ‐pro)] ( Δ‐ D ) diastereomer in the presence of O 2 with a blue light irradiation.…”
Section: Background and Originality Contentmentioning
confidence: 99%